On the veneration of “avvakums” in Pustozerskaya volost - Elena G. Menshakova (Российский журнал истории Церкви, 2022)
The publication on concrete facts reveals the tradition of veneration of the ideologists of the early Old Believers — Archpriest Avvakum “with goods” among the local citiazens officially belonged to the Orthodox Chuch (Synodical period) at the place of their execution in the Arctic Pustozersk and its surroundings (now the territory of the Nenets Autonomous Okrug) from the end of the 17th century to the first third of the 20th century.